2023
DOI: 10.1088/1402-4896/ace290
|View full text |Cite
|
Sign up to set email alerts
|

Physics-informed neural networks for solving nonlinear Bloch equations in atomic magnetometry

Abstract: In this study, we address the challenge of analyzing spatial spin distribution based on the nonlinear Bloch equations in atomic magnetometry through the use of physics-informed neural networks (PINNs). Atomic magnetometry plays a crucial role in the field of biomagnetism, where it is used to detect weak magnetic fields produced by the human brain, heart, and other organs. The Bloch equations describe the spin polarization of atomic clusters in an external magnetic field, but their nonlinearity can make the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Forward and inverse problems found in differential equations can both be solved using PINNs [8][9][10]. PINNs are also efficient in solving non-linear partial differential equations which are sometimes challenging to handle using traditional methods [11][12][13]. It is observed that specific issues associated with dimensionality in the area of numerical analysis of differential and dynamical systems are resolved with the help of PINNs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Forward and inverse problems found in differential equations can both be solved using PINNs [8][9][10]. PINNs are also efficient in solving non-linear partial differential equations which are sometimes challenging to handle using traditional methods [11][12][13]. It is observed that specific issues associated with dimensionality in the area of numerical analysis of differential and dynamical systems are resolved with the help of PINNs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A notable development is the introduction of automatic differentiation [1], which makes it possible to bypass numerical discretization and mesh generation, leading to a new machine learning-based technique known as PINN [2,3]. Since the introduction of the PINN, it has been widely used to approximate solution to PDE [4][5][6][7][8][9][10][11][12][13][14][15][16], particularly highly nonlinear ones with non-convex and oscillating behavior, such as Navier-Stokes equations, that pose challenges for traditional numerical discretization techniques. The problematic part of Navier-Stokes equations is because of the convective term in the equations introduces a nonlinearity due to the product of velocity components.…”
Section: Introductionmentioning
confidence: 99%